Assistance in Developing Interactive Assessments Based on Liveworksheets for Junior High School Teachers - Mohammad Nurwahid; Kurratul Aini; Makbul Muksar; Imam Rofiki; I Nengah Parta; Andi Daniah Pahrany (International Journal of Public Devotion, 2026)
This community service activity aimed to improve teachers’ understanding and skills in developing interactive assessments using Liveworksheet at SMP Al Hidayah Malang. The activity was conducted through workshops using lectures, demonstrations, hands-on practice, and mentoring methods. The participants consisted of 9 teachers from various subjects. Data were collected through pre- and post-workshop questionnaires, open-ended responses, and participants’ products. The results showed an improvement in teachers’ understanding and skills after participating in the workshop. All participants (100%) successfully created interactive assessments using various Liveworksheet features such as multiple choice, matching, drag-and-drop, and checkbox. In addition, participants gave positive responses to the workshop because it was considered beneficial in improving their knowledge and skills in educational technology. Therefore, the workshop on developing interactive assessments based on Liveworksheet proved effective in improving teachers’ competencies in digital assessment development.Pendampingan Penyusunan Asesmen Interaktif Berbasis Liveworksheet Bagi Guru Sekolah Menengah PertamaABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan keterampilan guru dalam menyusun asesmen interaktif berbasis Liveworksheet di SMP Al Hidayah Malang. Kegiatan dilaksanakan dalam bentuk workshop dengan metode ceramah, demonstrasi, praktik langsung, dan pendampingan. Subjek kegiatan terdiri atas 9 guru dari berbagai mata pelajaran. Data diperoleh melalui angket pre dan post workshop, pertanyaan terbuka, serta hasil produk peserta. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan guru setelah mengikuti workshop. Seluruh peserta (100%) berhasil membuat asesmen interaktif berbasis Liveworksheet dengan variasi fitur seperti pilihan ganda, menjodohkan, drag and drop, dan checkbox. Selain itu, peserta memberikan respons positif terhadap pelaksanaan workshop karena dinilai bermanfaat dalam meningkatkan wawasan dan keterampilan penggunaan teknologi pembelajaran. Dengan demikian, workshop penyusunan asesmen interaktif berbasis Liveworksheet terbukti efektif dalam meningkatkan kompetensi guru dalam pengembangan asesmen digital.Kata Kunci :Asesmen Interaktif; Liveworksheet; Workshop; Kompetensi Guru; Pengabdian Masyarakat